Ethyl 2-acetoxymethyl-1-phenylsulfonyl-1H-indole-3-carboxylate - Gunasekaran, B. (International Union of Crystallography, 2009)
In the title compound, C(20)H(19)NO(6)S, the phenyl ring of the phenylsulfonyl group makes a dihedral angle of 83.35 (5)° with the indole ring system. The molecular structure exhibits a number of short intramolecular C—H⋯O contacts.